The resettled Ati families in Buruanga, Aklan. - Tan, Shella Mae M.
This research project is about the Resettled Ati families in Buruanga, Aklan. It raises mquestions concerning their origin, factors of resettlement from Brgy. Cabugan to Brgy. Katipunan. This research aims to present the ethnography of the said Ati Community, to compare the present settlement-Brgy. Katipunan and former settlement Brgy. Cabugan, to determine the factors of their resettlement and to determine their problems, difficulties and social status., In doing the study the researcher relied on field interviews and immersion in the Ati community. Library and Internet research were also used for teh basic concepts of this study. The resettled Ati families in Buruanga, aklan have been through a number of resettlements, which caused by various reasons such as livelihood and living condition, in the past these rettlements were done without any assistance from outside institutions. Moreover, Atis did not resettle as a community. On the other hand, their recent resettlement in Brgy. Katipunan is a conscious effort of the Atis to organize themselves as a community with the help of a religious institution. This resettlement was also caused by various factors involving their former settlement- Brgy. Cabugan and present settlement, which is at Brgy. Katipunan. Upon their resettlement in Brgy. Katipunan, they are befaced with problems and difficulties, which the Atis perceive as challenges on their step toward an orgnized and progressive community. Despite their confused social status in the present society, Atis have high hopes that in their resettlement area, they could build a better future for their children.